Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1972
DOI: 10.1111/j.1365-3059.1972.tb01723.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fungicides on Leaf Diseases and on Yield in Spring Barley in South‐west England

Abstract: Summary In nine experiments in 1966–68, fungicides applied on 8–12 occasions to plots of barley resulted in mean grain yield increases of about 40 per cent. Zineb increased yields by an average of 50 per cent in nine experiments and lime sulphur by 19 per cent in six experiments. In single experiments dichlofluanid increased yields but oxycarboxin did not. In 1968, fungicides applied on only two occasions failed to control disease and to increase grain yield. Large yield increases were associated with a good c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Although this effect was attributed to fungicide treatment, the yield increase by the Folicur application was unlikely due to the control of leaf diseases, since the severity of leaf spotting diseases was very low. Similarly, Dickinson and Wallace (1976) and Jenkins et al (1972) reported that yield increases using zineb (a contact fungicide) were partly due to factors other than direct effects on the leaf pathogens, in wheat and barley (Hordeum vulgare L.), respectively. Kettlewell and Davies (1982) found that yield increase of wheat following application of Tilt (propiconazole, a systemic fungicide) was not directly related to disease control, but was associated with a higher photosynthetic rate.…”
Section: Resultsmentioning
confidence: 99%
“…Although this effect was attributed to fungicide treatment, the yield increase by the Folicur application was unlikely due to the control of leaf diseases, since the severity of leaf spotting diseases was very low. Similarly, Dickinson and Wallace (1976) and Jenkins et al (1972) reported that yield increases using zineb (a contact fungicide) were partly due to factors other than direct effects on the leaf pathogens, in wheat and barley (Hordeum vulgare L.), respectively. Kettlewell and Davies (1982) found that yield increase of wheat following application of Tilt (propiconazole, a systemic fungicide) was not directly related to disease control, but was associated with a higher photosynthetic rate.…”
Section: Resultsmentioning
confidence: 99%
“…(11,13,15,92,101,119,149,151). Significant yield losses have been reported from New Zealand (5), Australia (20), North America (46,81), the Czech Republic (29), the United Kingdom (56,83), Ethiopia (118), and South Africa (135). Murray & Brennan (86) estimated that in Australia the disease causes economic losses of AUD$9 million per year.…”
Section: Economic Importancementioning
confidence: 99%
“…National surveys, first of spring barley and then of winter wheat, were established to identify the major diseases (King, 1972;. Large & Doling (1962) measured the effects of cereal mildew (Erysiphe graminis) on yield, and Jenkins et al (1972) examined the use of fungicides for the control of diseases of spring barley in south-west England. Intermittent surveys of diseases in horticultural crops were also undertaken (Fletcher & Harris, 1979).…”
Section: ±81mentioning
confidence: 99%